Teacher Professionalism in the Context of Educational Management in the Digital Era - Marpaung, Irfan Satya Prasaja; Prajanti, Sucihatiningsih Dian Wisika; Pramono, Suwito Eko; Hidayah, Isti (Universitas Negeri Semarang, 2024)
Education is one of the main sectors related to the intelligence of the nation's life. Teacher professionalism is a critical factor in determining the quality of education. The purpose of this study is to analyze the level of teacher professionalism in managing digital-based learning, analyze the effectiveness of digital technology utilization by teachers in creating innovative and interactive learning, and analyze the gap between teachers' abilities in managing conventional learning and digital-based learning. This research uses a literature review method with a descriptive qualitative approach. Findings Teacher professionalism in managing digital-based learning is essential for the effectiveness of education in the digital era. Teacher professionalism, digital competency development, and interaction with the digital world are important to improving the quality of digital-based learning. Training, infrastructure investment, resource development, and inclusive learning models can address teacher capability gaps. Improving teachers' professionalism in managing digital learning is key to improving the quality of education in the digital era. Teachers must support students' learning process and develop critical skills, innovation, and collaboration through digital technology. Improving teachers' professionalism in managing digital-based learning in the digital era is key to improving the quality of education and meeting the demands of the times. This research is useful for improving the quality of education in the digital era. Teachers understand digital competencies and are motivated to improve their skills. The gap between teachers' abilities in conventional and digital learning is narrowed. Teachers are equipped with the knowledge and skills to become successful educators in the digital era.